Association between stroke and fracture and the mediating role of depression: a cross-sectional study from NHANES 2017 to 2020 - Dan, Yuqin; Pei, Xuewen; Xu, Danghan; Liu, Zhaoxi; Wang, Yuqi; Yin, Meng; Li, Li; Yu, Gongchang (Frontiers in Neurology, 2025)
BackgroundStroke is a significant health threat, and its complex interplay with fractures warrants further investigation. Depression, a critical psychological mediator in various health conditions, may also play a role. This study aims to clarify the intricate relationships among stroke, depressive symptoms, and fracture risk, potentially informing more holistic clinical strategies.MethodsUtilizing the most recent data from the National Health and Nutrition Examination Survey (NHANES, 2017 to 2020), this study encompassed 4,979 valid samples. T-test and chi square test are conducted to compare the differences between fracture and non fracture subgroups. Subsequently, regression models were applied to assess the mediating impact of depression, with Sobel’s test and the bootstrap method deployed to substantiate the mediation pathways.ResultsIn this study, we conducted subgroup and regression analyses to investigate factors influencing fractures in stroke patients using NHANES data. Subgroup analysis revealed significant associations with gender, race, osteoporosis, and depression. Female stroke patients had a higher fracture rate (73.86% vs. 47.78%, p < 0.001), and those with post-stroke depression (29.67% vs. 13.16%, p < 0.001) or osteoporosis (33.33% vs. 15.81%, p < 0.05) were at increased risk of fractures. Logistic regression models showed a positive association between stroke and fractures in the unadjusted (OR = 1.862, 95% CI: 1.348–2.573, p < 0.001) and adjusted I models (OR = 1.789, 95% CI: 1.240–2.581, p < 0.01), but not in the adjusted II model. Depression was significantly correlated with fractures in all models (unadjusted OR = 2.785, 95% CI: 1.271–6.101, p < 0.05; Model 1 OR = 3.737, 95% CI: 1.470–9.498, p < 0.01; Model 2 OR = 3.068, 95% CI: 1.026–9.175, p < 0.05). Mediation analysis using Sobel and bootstrap tests indicated that depression mediates 7.657% of the relationship between stroke and fractures (Z = 2.31, p < 0.05), with significant indirect (Z = 2.80, p < 0.01), direct (Z = 3.61, p < 0.001), and total effects (Z = 3.92, p < 0.01). The direct effect of stroke on fracture was 0.079 (95% CI: 0.036–0.121), the total effect was 0.085 (95% CI: 0.043–0.128), and the indirect effect mediated by depressive symptoms was 0.007 (95% CI: 0.002–0.011). These results suggest that depressive symptoms following stroke may contribute to an increased risk of fractures.ConclusionDepressive symptoms serve as a critical mediator in the link between stroke and fracture risk. Consequently, our study concludes that holistic prevention strategies for fractures in stroke patients must incorporate a focus on mental health to effectively address this complex clinical challenge.